Perencanaan lanskap ruang terbuka sebagai fungsi edukasi di lingkungan pendidikan SMA Kornita Bogor - I Made Bagus Dwi Sucipta; Anak Agung Keswari Krisnandika; I Made Agus Dharmadiatmika (Jurnal Arsitektur Lansekap, 2025)
Open space landscape planning plays an important role in supporting educational functions within the Kornita High School environment. Kornita High School is the only secondary school located within the campus of IPB University (Bogor Agricultural University), in Dramaga, Bogor. As the school's range of activities becomes increasingly diverse, the demand for space continues to grow. Several issues have emerged, including limited parking areas, building damage caused by sports activities, and the presence of venomous animals and wild primates. These problems stem from the lack of proper spatial planning based on landscape architectureprinciples, particularly in the management of open spaces. This study adopts a student activity-based approach to improve the accuracy of planning. The objective is to identify, analyze, and propose planning solutions that support educational activities at Kornita High School, based on the planning theory of Simon and Starke. The research method employed is a survey, utilizing both qualitative and quantitative descriptive analyses. Data collection was conducted through observation, interviews, and literature review. Observations reveal that abandoned open spaces—lacking routine maintenance such as pruning—have contributed to the presence of wild animals. Interviews indicate that comfort and safety in parking areas and sports fields need improvement, and that studentsrequire open spaces for artistic and creative activities. The study resulted in a site plan developed under the concept of a “Learning Resource,” which is manifested through the inclusion of greenhouses, fruit gardens, outdoor learning areas, green corners, sports fields, and small-scale (alit) theaters.